Развитие русской портретной живописи XVIII века. Ф. С. Рокотов, Д. Г. Левицкий - - Кузьминский К. С. Константин Станиславович (Антология мысли)
URL: https://urait.ru/bcode/565628 (дата обращения: 27.08.2025).